Health-Related Quality of Life Survey in Persons with Disabilities, Thailand, 2015 - Suvapan, Daranee; Loharjun, Bootsakorn; Sunsern, Rachanee; Lawang, Wannarat; Phothong, Chiraphun; Srisuppaphon, Donruedee; Kaewsawang, Sarinee; Solunda, Suleepun (Journal of Health Science of Thailand, 2018)
The ultimate goal of rehabilitation is to improve quality of life (QOL) of persons with disabilities. However, QOL of persons with disabilities is usually measured in healthcare facilities. Thus, there is limitation of information on different groups of persons with disabilities. Moreover, large scale studies are scarce. This study aims to quantify level of QOL of Thai persons with disabilities. From July to December 2015, a survey with constructed questionnaire was carried out on 15,110 persons with disabilities in 25 provinces. World Health Organization Quality of Life (WHOQOL-BREF-THAI) was applied to deter mine the QOL while socio-demographic characteristics, geographic characteristic, health status, family factor and type of disability were also obtained. Descriptive analysis was used. Overall score and the score of different domains in different groups of disability were compared. The participants had a mean age of 54.3 years (SD = 20.5). The majority had middle level of QOL (mean = 86.3 ฑ . ). One-fifth of persons with disabilities had poor QOL in social relations. QOL of persons with autism and persons with more than one disability type were lower than average. Therefore, policies and strategies in rehabilitation should include measures to facilitate social relations and vocational rehabilitation. Strategies toward per sons with autism and persons with more than one type of disability should be particularly prioritized.